2007
DOI: 10.1161/hypertensionaha.107.088948
|View full text |Cite
|
Sign up to set email alerts
|

Prostaglandin E 2 Induces Vascular Relaxation by E-Prostanoid 4 Receptor-Mediated Activation of Endothelial Nitric Oxide Synthase

Abstract: Abstract-The present experiments were designed to test the hypothesis that prostaglandin (PG) E 2 causes vasodilatation through activation of endothelial NO synthase (eNOS). Aortic rings from mice with targeted deletion of eNOS and E-prostanoid (EP) receptors were used for contraction studies. Blood pressure changes in response to PGE 2 were measured in conscious mice. Single doses of PGE 2 caused concentration-dependent relaxations during contractions to phenylephrine (EC 50 ϭ5*10 Ϫ8 mol/L). Relaxation after … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
93
1
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 108 publications
(100 citation statements)
references
References 29 publications
(21 reference statements)
5
93
1
1
Order By: Relevance
“…Increasing evidence indicates that the vascular and renal actions of PGE 2 may be mediated by NO, 15,27 raising a possibility that the NO-cGMP pathway may be affected in mPGES-1 Ϫ/Ϫ mice. We found that Ang II-induced hypertension in mPGES-1 Ϫ/Ϫ mice was associated with a significant reduction of urinary NO x excretion that was restored by Tempol treatment.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Increasing evidence indicates that the vascular and renal actions of PGE 2 may be mediated by NO, 15,27 raising a possibility that the NO-cGMP pathway may be affected in mPGES-1 Ϫ/Ϫ mice. We found that Ang II-induced hypertension in mPGES-1 Ϫ/Ϫ mice was associated with a significant reduction of urinary NO x excretion that was restored by Tempol treatment.…”
Section: Discussionmentioning
confidence: 99%
“…In most vascular beds, PGE 2 serves as a physiologically important vasodilator. 27,28 However, PGE 2 is a potent vasoconstrictor in the tail artery 29 and mesenteric arteries. 30 The vascular effects of PGE 2 is also species dependent.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…35) The PGE 2 -induced relaxations were mimicked by an ONO-AE1-329 in aortic rings. 36) Recently, we developed a novel EP4 selective agonist (EP4RAG) ( Figure 1H). The EP4RAG was selectively bound to the murine EP4 receptor.…”
Section: Synthesized Ep Agonists I) Ep1 Agonistsmentioning
confidence: 99%
“…3) Furthermore, blood flow is regulated by various factors such as nitric oxide (NO) 4) and prostanoids, 5) and the autonomic nerve system. 6) NO plays important roles including causing vasodilatation in the endothelium and controlling physiological conditions.…”
mentioning
confidence: 99%